Development of Puzzle-Based Modules on Solar System Topics to Increase Learning Motivation of Junior High School Students - Rahmad, Afan; Sholihat, Neng; Sholihat, Agusminarti (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2024)
This research aims to develop a puzzle-based module on solar system material to increase the learning motivation of class VII junior high school students. This Research and Development (R&D) uses the ADDIE model development stage in developing puzzle-based modules by combining several types of puzzles, such as spelling puzzles, crossword puzzles, and the thing puzzle. The research subjects were 23 class VII students at SMP Muhammadiyah 1 Pekanbaru. Data was collected using validation sheets, practicality questionnaires, and student learning motivation questionnaires. The data analysis techniques used were validity analysis, practicality, and motivation questionnaire analysis before and after using the puzzle-based module. The research results show: 1) The feasibility of the puzzle-based module is 90% by material experts and 86% by media experts, 2) The puzzle-based module developed is stated to be very practical with a percentage of 94%, 3) The average percentage of the overall initial motivation of students before using a puzzle-based module was 55.74, while the final motivation after using the module was 81.61. The average increase in students' learning motivation was 25.87 and the average N-Gain was 0.59 in the medium category. Therefore, it is concluded that using puzzle-based modules on solar system material in the learning process can increase the motivation of class VII students at SMP Muhammadiyah 1 Pekanbaru.